Gender, medicalization and power. Feminization in the medical profession because the proletarianization profession (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2019)
Medical knowledge is for men, other knowledge about health, as biochemistry or nursing can oversee women. This affirmation of common sense is constantly contradicted by the statistics that show that the medical profession is currently exerted mostly by women. We talk about doctors, men, and nurses, women. The association between medical knowledge and power, imposed hegemonically in the nineteenth century, became part of the common sense culturally transmitted and maintains its validity. In a capitalist society, dominated by the market even in the innermost aspects of private life, health, as an ethical value, gave way to health as a mercantile value.We seek to investigate the social conditions of production and correlate the displacement of the medical profession of males towards women with displacement from a high bourgeoisie oligarchic towards a proletariat.From the nineteenth century until today, the medical profession step of being exerted by males and some few women of the dominant elite to be the profession of the middle class accommodated in the first half of the XX until being exerted by professionals who work in piece; at the beginning of the 21st century. We attribute a strong correlation of this gender displacement to class displacement and today the prevalence of women is greater than of males and to differential parenting conditions between boys and girls.
Keywords: gender; doctors; class; human resources; workers